2021
DOI: 10.1097/mpg.0000000000003311
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Gastrointestinal, Hepatic and Pancreatic Inflammatory Myofibroblastic Tumours, A Single Centre Experience

Abstract: Inflammatory myofibroblastic tumours (IMTs) are rare soft tissue tumours. Reports of gastrointestinal tract, liver and pancreas tumours are limited. The objective of this study is to identify presenting features, contributing prognostic / etiological factors and any variability in outcomes in the context of different historical treatments. We retrospectively reviewed the records of seven children treated at our hospital between 2006 and 2019 and assessed the demographic, presentation, treatment, immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Curative resection remains the primary treatment modality for myofibroblastic tumors. 29 According to Meng et al grade 1 MS should be managed with wide excision and long‐term follow‐up, and grade 2 MS should be managed by excision with a wide margin of normal tissue and adjuvant radiation therapy or systemic chemotherapy. 3 Casanova et al reported that IMT patients treated with full surgical resection had excellent outcomes and required no adjunctive therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curative resection remains the primary treatment modality for myofibroblastic tumors. 29 According to Meng et al grade 1 MS should be managed with wide excision and long‐term follow‐up, and grade 2 MS should be managed by excision with a wide margin of normal tissue and adjuvant radiation therapy or systemic chemotherapy. 3 Casanova et al reported that IMT patients treated with full surgical resection had excellent outcomes and required no adjunctive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…31 Postoperative radiotherapy has been reported to be potentially effective in MS. 32 For locally advanced or metastatic myofibroblastic tumors, chemotherapy and radiotherapy can be considered. 29 Notably, alterations of the ALK gene are the predominant molecular characteristics of IMTs. 33 The ALK inhibitor crizotinib is, therefore, a recommended targeted agent for the treatment of IMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation